The Use Of Scientific Approach Based Physics Module In Themperature And Kalor Subject To Improve Student’s Activities And Physic Cognitive - Setyanisa, Lia; Sukarmin, Sukarmin; Rahardjo, Dwi Teguh (PAEDAGOGIA, 2020)
Research has the intention to; increase students' physics learning activities; improve students' cognitive abilities in Physics by using Physics Approach modules based on Scientific Approach for temperature and heat. The subjects of the study were 36th grade MIA 4 students of Kebakkramat Karanganyar State High School in the 2014/2015 academic year 2014/2015 with a total of 36 students. Based on data analysis and discussion in this study it can be concluded that: Physics learning through the use of Physics Approach modules based on Scientific Approach of temperature and heat material can increase Physics learning activities. In the first cycle has increased but only two aspects of learning activities have reached the success target while the other five aspects have still not reached the success target. In the second cycle all aspects of learning activities have increased and achieved success targets. Physics learning through the use of Physics Approach-based Physics Approach modules temperature and heat material can improve the cognitive abilities of Physics, can be seen from the results in the first cycle of students completeness by 33.3% and in the second cycle has increased to 80.6%. The target of cognitive performance is the completeness of students reaching 70%.